Pneumatic dilatation in achalasia. Issue 11 (November 1983) - Fellows, I W; Ogilvie, A L; Atkinson, M
Abstract : To assess the value of pneumatic dilatation of the cardia, 63 patients with achalasia have undergone a total of 107 Rider-Moeller dilatations over the last six years. There was a marked improvement in swallowing immediately after dilatation in all but two patients, there were no deaths attributable to the procedure and serious complications were rare (1.6% of patients). The first 50 cases have been followed from nine to 73 months after their initial dilatation (mean follow-up 29.7 months). Twenty nine patients (58%) have not required a further dilatation, 19 patients (38%) required between one and three further dilatations and two patients (4%) required four more dilatations. Continuing need for further dilatation was significantly greater in those patients aged under 45 years than in those aged 45 or more at the time of their initial dilatation (p less than 0.001). Cardiomyotomy was necessary in five patients (10%), because of poor response to pneumatic dilatation; all five cases were under 45 years old at their initial dilatation. Pneumatic dilatation is a safe and effective treatment for achalasia, particularly in the older patient, and in our opinion should be the initial treatment for all patients with achalasia, reserving surgical cardiomyotomy for those who do not respond to several dilatations.